Techniques for stress reduction in the clinical care of dogs and cats during veterinary consultation - Pozzatto, Débora de Souza; Vieira, Jhulya de Andrade Borges; Moreira, Luciano de Paulo; Ventura, Bruno Passagem; Vale, Isabelly Santos; Pedrosa, Poliana Laviola; Aptekmann, Karina Preising (Pubvet, 2022)
Dogs and cats can suffer acute stress during veterinary clinical care. As a consequence, the clinical examination of the patient may be impaired, and some complementary tests may be influenced by stress and present alterations, with prejudice to their interpretation. In addition, the generation of stress can reduce the frequency with which pets are taken to the veterinary consultation and the guardian’s adherence to treatment. In addition, it increases the risk of accidents, such as bites and scratches, and the animal is negatively conditioned. For this reason, it is important to know the body language of dogs and cats in the clinical routine, to know how to interpret them according to the situation, and to know how to act when faced with them. Preparing the environment to receive animals in a more friendly way is also essential to reduce the stress level of dogs and cats undergoing veterinary care. Therefore, the objective of this study was to carry out a literature review on techniques to reduce stress in the clinical care of dogs and cats.